The Influence of Entrepreneurship Education and Business Incubation on Entrepreneurial Interest with Family Environment as a Mediating Variable Among High School Students in Central Jakarta Region II - Reflino, Oneal Sandros; Mulyadi, Hari; Sojanah, Jannah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Entrepreneurship plays a crucial role in fostering innovation, reducing unemployment, and strengthening national economic resilience. In Indonesia, the integration of entrepreneurship education with school-based business incubation programs has become increasingly important, particularly in addressing the high unemployment rate among high school graduates. This study examines the influence of Entrepreneurship Education (X1) and Business Incubation (X2) on Entrepreneurial Interest (Y), with Family Environment (Z) functioning as a mediating variable among private high school students in Central Jakarta Region II. Using a quantitative survey method, data were collected from 371 students selected through simple random sampling from a population of 4,940 students participating in entrepreneurship programs and school incubators. Structural Equation Modeling (SEM) was applied to test the measurement and structural models, including direct, indirect, and mediation effects. The results show that both entrepreneurship education and business incubation have significant positive effects on students’ entrepreneurial interest. Entrepreneurship education enhances students’ knowledge, skills, and confidence, while incubation programs strengthen practical experience through mentoring, project-based activities, and exposure to real business environments. The family environment also demonstrates a significant mediating effect by reinforcing students’ entrepreneurial motivation through emotional support, role modeling, and encouragement. These findings align with major theoretical frameworks, including the Theory of Planned Behavior, Social Learning Theory, and Entrepreneurial Learning Theory, which emphasize the interplay of education, experience, and social context in shaping entrepreneurial intentions. Overall, the study highlights the importance of strengthening school-based incubation and fostering family involvement to develop competitive young entrepreneurs capable of contributing to economic development.